Analysis of the coseismic slip behavior for the MW = 9.1 2011 Tohoku-Oki earthquake from satellite GOCE vertical gravity gradient - Álvarez, Orlando; Gimenez, Mario; Folguera, Andrés (Frontiers in Earth Science, 2022)
Over the past decade, the three largest and most destructive earthquakes in recent history with associated tsunamis occurred: the 2004 Mw=9.2 Sumatra-Andamam, then the 2010 Mw=8.8 Maule and finally the 2011 Mw=9.1 Tohoku- Oki. Due to the technological and scientific developments achieved in recent decades, it has been possible to study and model these phenomena with unprecedented resolution and precision. In addition to the co-seismic slip models depicting the space-time evolution of the rupture, we have high resolution models of the degree of interseismic coupling and also maps of seismic b-value changes. Among these advances, new Earth gravity field models allow mapping densities distribution homogeneously and with a resolution of approximately the large rupture areas of great megathrust earthquakes. From the study of the static and dynamic gravitational field, it has been possible to infer mass displacements associated with these events, which have been modelled and compared to the deformation inferred by means of other methods, yielding very good results. In this work we study the kinematic behaviour of the rupture process for the 2011 Mw=9.1 Tohoku-Oki earthquake, by means of the vertical gravity gradient derived from the GOCE satellite, finding that the maximum slip occurred close to a lobe of minimum Tzz, as was observed for other case-studies in other subduction-related settings studied in previous works (e.g., the Maule earthquake and the Sumatra-Andaman earthquake, among others). In addition, from the rupture propagation by means of kinematic models, it can be observed that the rupture is arrested when it approaches to high-density structures and, it is enhanced when connecting with lobes of low vertical gravity gradient. We also mapped a block expressed as a low Tzz lobe, developed along the marine forearc, which is controlled by a parallel-to-the-trench normal fault that accommodates subsidence during the interseismic period, as it is coupled with the subducted slab. Then, after rupturing the plate interface, this block is decoupled in the co-seismic, promoting tectonic inversion and uplift. In this way, the hypothesis that the density structure along the forearc is the ultimate first-order factor that governs the rupture process is reinforced.